Moroccan High-school Students’ Attitudes towards Learning English as a Foreign Language - Layla Aknouch (Institut Agama Islam Negeri Palopo, 2023)
The process of learning a language is influenced by a number of factors. One of the most significant factors that has an influence on learning a language is attitude. Research in this area has demonstrated that learners’ attitudes are a constituent and crucial part of the learning process. As such, learners’ attitudes towards language should be dealt with as a critical component of second and foreign language learning pedagogy. Accordingly, the current study addresses the attitudes of Moroccan high-school students towards learning English as a foreign language. Specifically, the study aims to investigate Moroccan high-school students’ attitudes towards English, the reasons behind their attitudes and the impacts that such attitudes might potentially have. Generally speaking, the study found that the participants have highly favourable attitudes towards learning English for different reasons, a fact that results in positive impacts on students’ willingness to learn the language.Keywords: Attitudes; Language; EFL context